Pembentukan Karakter Peduli Lingkungan pada Mahasiswa PPKn melalui Pendekatan Green Constitution - Sukmawati; Rahma Nasir; Mustari (Universitas Tadulako, 2022)
Character values ​​can be attached to students through learning and habituation (habituations) for students to love and care for the campus environment so that they are expected to become student characters. The learning in PPKn based on the Green Constitution is expected to raise the rights and obligations of citizens as contained in the constitution and other laws that discuss environmental conservation. This research was conducted in the third semester of students in the study program of PPKn, Teacher Training and Education Faculty Tadulako University, totaling 75 people consisting of 2 classes. Data were collected by giving pretest and posttest questions. The pretest is given to students in the form of the multiple-choice written test. Before the treatment was given, the initial condition of the students still showed a bad habit such as littering in the classroom and outside the classroom. Students are apathetic by not taking the initiative to immediately pick up or clean up trash. This condition indicates that students still lack a sense of belonging to a clean environment. The success rate of student learning in the pretest, which is 72%, is categorized as very low and after being given material on the Green Constitution are 94.6% of students understand the concept of caring for the environment.